Kinetics and thermodynamics of Cr (VI) reduction by Tamarindus indica methanol leaves extract under optimized reaction conditions - Babangida Sanusi Katsayal; Abdullahi Balarabe Sallau; Aliyu Muhammad (Beni-Suef University Journal of Basic and Applied Sciences, 2022)
Abstract Environmental contamination with Cr (VI) has recently attracted public attention because of its high concentration in soil and wastewater originating majorly from anthropogenic activities and natural processes. Reduction of Cr (VI) to Cr (III) is a feasible method for minimizing chromium pollution. This work aimed at characterizing the effects of Cr (VI) reduction conditions in a batch experiment such as temperature, hydrogen ion concentration, time, and reactant concentrations, as well as kinetics and thermodynamics of the reaction using Tamarindus indica methanol leaves extract as a reductant. Cr (VI) reduction was meaningfully affected by temperature, hydrogen ion concentration, reaction time, and reactant concentrations. The reaction followed the pseudo-second-order kinetic model (R 2 = 0.997) at pH of 2; at the neutral and alkaline pH (7 and 9), the reaction predominantly obeyed first order (R 2 = 0.988) and pseudo-first order (R 2 = 0.758), respectively. Under various hydrogen ion concentrations, the reaction retains negative free energies, enthalpy change, and a positive entropy. The findings from this study suggested the reaction to be spontaneous, exothermic, and orderly unstable. We concluded that phytocompounds present in tamarind methanol leaves extract demonstrated a strong potentials for converting Cr (VI) to Cr (III) and, thus, could be applicable in Cr (VI) contaminated wastewater treatment.